Collaborative Governance and New Public Service in Realizing a Single Source of Truth: Evidence from the SIPEDULI and JSDDD Programs in Jembrana Regency - I Gede Sudiadiarta; Gusti Ayu Agung Dewi Sucitawathi Pinatih (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
In the era of digital disruption, an agile and responsive bureaucracy is essential to improve governance and public service delivery. The Government of Jembrana Regency has implemented the Online Population Administration Service System (SIPEDULI) and the Jembrana One Data from Villages program to support digital services and village-level data governance. This study aims to evaluate the effectiveness of SIPEDULI, assess the quality of population data, and analyze collaborative governance dynamics in achieving a Single Source of Truth at the village level. Using a descriptive qualitative approach, data were collected through interviews, observation, and document analysis. The analysis integrates perspectives on e-government effectiveness, data quality, collaborative governance, and New Public Service principles. The findings show that SIPEDULI has improved service accessibility and efficiency. However, its contribution to enhancing data validity remains limited due to weak system integration and insufficient coordination among stakeholders. Collaborative governance has not been fully institutionalized, and community participation in data updating is still largely administrative rather than substantive. These results imply that achieving a reliable Single Source of Truth requires stronger system integration, improved inter-organizational collaboration, and enhanced digital capacity at the village level. Additionally, reinforcing participatory and citizen-centered service principles is crucial to ensure sustainable data governance and higher data accuracy in public administration.